IDENTIFICATION OF PROBLEMS IN THE PROCESS OF FORMING AN EFFECTIVE REGIONAL MANAGEMENT SYSTEM IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. Attention is focused on the activation of the waste processing process, the technical equipment of the functional elements of the regional waste management system, the use of foreign experience in the implementation of recycling capacities, which will make it possible to specify goals in the implementation of innovative tasks in this field. The reasons that led to the low level of development of the domestic sphere of waste management are singled out: ineffective environmental policy, insufficient financing of relevant measures, neglect of environmental requirements, lack of practical steps in the development of infrastructure of a utilization nature. The purpose of the article. The purpose of the article is to identify problems that occur in the process of forming a regional waste management system in Ukraine, which prevent the achievement of real results in the context of sustainable development of regions. In order to achieve the set goal, the task of determining: a) problems that occurred before the full-scale war of 2022 was solved; b) problems that were added in the conditions of martial law. Results. It is emphasized that the formation of an effective waste management system is an important component of qualitative changes (sustainable development) in the regions of Ukraine in the context of its European integration aspirations. The region was considered in the context of obligations to eliminate existing problems in the field of waste management and practical implementation of tasks defined in regional waste management plans. A number of problems that occur in the field of waste management at the regional level are highlighted. The legislative provision of the waste management system and its influence on the achievement of expected results in this field are analyzed. The capabilities of local authorities in developing infrastructure for waste processing are substantiated. The treatment of waste in the conditions of martial law was studied. It was determined that within the limits of particularly dangerous territories there is a need to focus on the management of waste from destruction, on relatively safe ones - on household waste. The problems associated with the functioning of existing waste processing facilities due to the crisis situation in energy supply are singled out. Conclusions. It is noted that the identified problems are issues that need to be resolved, as threats arise behind them; these are tasks that should be solved in the context of the National Waste Management Strategy in Ukraine until 2030 with the aim of forming/developing the waste management system; these are the goals that must be resolved in the context of sustainable development and the development of a cyclical economy.
Keywords: waste, waste management, problems, region, waste management, regional waste management system, utilization infrastructure.